Tracing the Negative Results of Multiplex Real-Time PCR Assay for Diagnosis of Bacterial Pediatrics Meningitis. (16th January 2023) - Karimi, Abdollah; Rafiei Tabatabaei, Sedigheh; Azimi, Leila; Almasian Tehrani, Nasim; Fallah, Fatemeh; Faghihian, Iman
Abstract : The death because of meningitis remains high in some parts of the world. It is important to know the specific cause of meningitis because the treatment differs depending on the cause. This study aimed to trace the false-negative results of multiplex RT-PCR to detect Streptococcus pneumoniae, Haemophilus influenzae, and Neisseria meningitidis serogroup by two different molecular methods. In this study, the CSF of the suspicious pediatric for acute bacterial meningitis among children aged 1 month to 14 years who are admitted to the hospitals in four cities of a certain region of Iran was collected. S. pneumoniae, H. influenzae, and N. meningitidis in CSF samples were detected by single-tube multiplex RT-PCR and specific RT-PCR with a probe on the same specimens. In this cross-sectional study, 506 CSF samples were collected during one year. The multiplex RT-PCR can detect 3.3% and 2.2% of S. pneumoniae and H. influenzae, respectively. N. meningitidis was not detected. The CSF analysis was abnormal in 53% of 506 patients. On the other hand, 11.5%, 4.8%, and 4.1% of S. pneumoniae, H. influenzae, and N. meningitidis were identified, respectively, by specific RT-PCR assay, exactly on the same specimens. Various types of PCR can be used for pathogen identification. As we change the type of PCR in our study, we could approximately increase 15% our positive results and also consequently decrease our false-negative responses.